Hrabivska H. “Halycko-ruska bibliographia XIX ct.” of I. Levitskiy on the pages of periodical “Kurjer lwowski” in Ivan Franko’s reflektion - Hrabivska H. (Philological Treatises, 2020)
All Ivan Franko’s notes concerning I.O. Levytskiy’s work «Halytsko-ruska bibliographia ХIX ct.» on the pages of periodical «Kurjer Lwowski» have been analzyed. The importance of Franko-publicist’s work for popularization of publishing activity of Galician bibliographer has been substantiated.